IDENTIFIKASI KERUSAKAN GAMBAR CADAS PADA SITUS GUA LA KOLUMBU DESA LIANGKABORI KECAMATAN LOHIA KABUPATEN MUNA - Cindi Claudia Arindi; Syahrun Syahrun; Arie Toursino Hadi (SANGIA: Jurnal Penelitian Arkeologi, 2024)
The Lakolumbu Cave site is one of the caves that has rock drawings. The site is in Liangkabori Village, Lohia District, Muna Regency, Southeast Sulawesi Province. This study aims to determine the image motifs and factors that cause damage to rock images at the Lakolumbu Cave Site. Then the methods used in this study were data collection, data recording and data processing using ImageJ software to lift images clearer and using CorelDraw X7 Software to reproduce rock images. Based on the results of the research conducted, the Lakolumbu Cave Site has 8 panels with a total of 60 rock images that have been found. The rock images are divided into 6 motifs including human motifs, animal motifs, human and animal motifs, human and boat motifs, geometric motifs and abstract motifs. Human motifs total 32 images. There are 8 animal motifs. Animal and human motifs total 13 images. 1 picture geometric motif. The motif of a man with a boat totalling 1 image. Abstract motifs totalling 4 images. The damage to the rock images found in Lakolumbu Cave is divided into 3 types of damage including temperature fluctuations, biological weathering and flaking.